Neonatal cardiac mitochondria and ischemia/reperfusion injury - Milerova, Marie; Charvatova, Zuzana; Skarka, Libor; Ostadalova, Ivana; Drahota, Zdenek; Fialova, Martina; Ostadal, Bohuslav (Molecular and cellular biochemistry, 2010)
Postnatal maturation of the heart is characterized by decreasing tolerance to ischemia/reperfusion (I/R) injury associated with significant changes in mitochondrial function. The aim of this study is to test the hypothesis that the role of the mitochondrial membrane permeability transition pore (MPTP) in the I/R injury differs in the neonatal and in the adult heart. For this purpose, the effect of blockade of MPTP on the degree of I/R injury and the sensitivity of MPTP to swelling-inducing agents was compared in hearts from neonatal (7 days old) and adult (90 days old) Wistar rats. It was found that the release of NAD(+) from the perfused heart induced by I/R can be prevented by sanglifehrin A (SfA) only in the adult myocardium; SfA had no protective effect in the neonatal heart. Furthermore, the extent of Ca-induced swelling of mitochondria from neonatal rats was significantly lower than that from the adult animals; mitochondria from neonatal rats were more resistant at higher concentrations of calcium. In addition, not only the extent but also the rate of calcium-induced swelling was about twice higher in adult than in neonatal mitochondria. The results support the idea that lower sensitivity of the neonatal MPTP to opening may be involved in the mechanism of the higher tolerance of the neonatal heart to I/R injury.
Keywords: spirosloučeniny; Animals, Newborn; Rats, Wistar; srdeční mitochondrie; Mitochondrial Membrane Transport Proteins; potkani Wistar; reperfuzní poškození; novorozená zvířata; transportní proteiny mitochondriální membrány; Mitochondria, Heart; krysa rodu Rattus; Animals; Mitochondrial Permeability Transition Pore; zvířata; Lactones; laktony; Rats; Spiro Compounds; přechodový pór mitochondriální permeability; Reperfusion Injury